Design of Flexible 3.2 GHz Rectangular Microstrip Patch Antenna for S-Band Communication - Teguh Praludi; Yana Taryana; Ken Paramayudha; Budi Prawara; Yusnita Rahayu; Chaeriah Bin Ali Wael; Yaya Sulaeman; Bagus Edy Sukoco; Ros Sariningrum; Hendrawan Kurniadin; Wahid Nova Nugraha (National Research and Innovation Agency, 2021)
This paper presents the design, simulation, realization and analysis of flexible microstrip patch antenna for S-band applications. The proposed design also adopts the conformal structure by utilizing flexible substrate. Conformal or flexible structure allows the antenna to fit with any specified shape as desired. The antenna patch dimensions is 43 mm × 25 mm without SMA connector. The patch is etched on the flexible dielectric substrate, pyralux FR 9111, with a relative dielectric constant of εr = 3 and the thickness of substrate, h = 0.025 mm. The antenna is designed to resonate at 3.2 GHz. The return loss (RL) of the simulation is -35.80 dB at the center frequency of 3.2 GHz. The fabricated antenna prototype was measured at different bending angles scenarios including 0º, 30º, 60º, and 90º. The measurement of antenna prototype shows that the center frequency is shifted to the higher frequency of 3.29 GHz, compared to the simulation result. Among these scenarios, measurement at bending angle of 90º gives the best performance with RL = - 31.38 dB at 3.29 GHz, the bandwidth is 80 MHz, and the impedance ZA = 48.36 + j2.04 Ω. Despite a slight differences from simulation results, the designed antenna still performs well as expected.